2020
DOI: 10.1007/s11192-020-03531-4
|View full text |Cite
|
Sign up to set email alerts
|

How scientific research reacts to international public health emergencies: a global analysis of response patterns

Abstract: As of the middle of April 2020, the unprecedented COVID-19 pandemic has claimed more than 137,000 lives (https://coronavirus.jhu.edu/map.html). Because of its extremely fast spreading, the attention of the global scientific community is now focusing on slowing down, containing and finally stopping the spread of this disease. This requires the concerted action of researchers and practitioners of many related fields, raising, as always in such situations the question, of what kind of research has to be conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
146
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(177 citation statements)
references
References 24 publications
16
146
0
6
Order By: Relevance
“…Although geopolitical tensions are ongoing, the extent of scientific globalism is generally higher in times of a global crisis and on the global crisis issue. The findings support past research that research productivity increases during public health emergencies (Zhang, Zhao, Sun, et al, 2020) and that most COVID-19 research is produced within countries, with China leading in COVID-19 publications (Hook & Porter, 2020;Hossain, 2020;Chahrour, Assi, Bejjani, et al, 202). Further analyses showed variations by countries and that while a country's prior patterns mattered in collaborating on internationally authored publications, the extent to which the country was affected by COVID-19 increases the likelihood they would participate in international collaboration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although geopolitical tensions are ongoing, the extent of scientific globalism is generally higher in times of a global crisis and on the global crisis issue. The findings support past research that research productivity increases during public health emergencies (Zhang, Zhao, Sun, et al, 2020) and that most COVID-19 research is produced within countries, with China leading in COVID-19 publications (Hook & Porter, 2020;Hossain, 2020;Chahrour, Assi, Bejjani, et al, 202). Further analyses showed variations by countries and that while a country's prior patterns mattered in collaborating on internationally authored publications, the extent to which the country was affected by COVID-19 increases the likelihood they would participate in international collaboration.…”
Section: Discussionsupporting
confidence: 87%
“…The countries most affected, however, do not produce the most articles; the countries with the highest number of publications in different areas were China (SARS), the US (Ebola), and Turkey (Crimean-Congo). The peaks in publication rates corresponded with the timeframe of the respective outbreaks, as was also found for COVID-19 publications (Zhang, L., Zhao, W., Sun, B. et al, 2020).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Zhang, L., Zhao, W. J., Sun, B. B., Huang, Y., & Glänzel, W. (2020) [11] discovered that academic community have often acted immediately to crises of global health with a substantial increase in the papers directly following the WHO's statement of pandemic. Study in the areas of virology, contagious diseases and immunology has been the most productive, and have found two speci c characteristics in world -wide science that differentiate studies in America and Europe that concentrates mostly on population health from that in Japan and China, with stronger focus respectively on biomedical research and clinical pharmacy.…”
Section: Related Literaturementioning
confidence: 99%
“…Europe and North America develop collaborative research with the main countries and with the outbreak regions, as observed with Ebola in Africa. SARS research is commonly conducted by China and the USA, with European countries' contributions relatively low 6 .…”
Section: Introductionmentioning
confidence: 99%